Loss of sovereignty: transfer of trading competences from member states of the European Union under the Maastricht Treaty- an example of regional integration - Bondt, Jan De (School For Advanced Legal Studies, 2026)
Policy before World War I, the Great War, was dominated by national independence, the aspiration to hegemony and the creation of spheres of interest. Europe's old national structures were deeply disrupted by the end of World War I. The idea of a voluntary union 6, not governed by the dictates of a sovereign of whatever kind, was born.